GASTRONOMY TOURISM AND THE PERCEIVED IMAGE OF SERBIAN NATIONAL CUISINE: STRUCTURAL EQUATION MODELING OF THE MAIN DETERMINANTS - Chroneos Krasavac, Biljana; Marinković, Veljko; Soldić-Aleksić, Jasna; Karamata Aćimović, Ema (Economics of Agriculture, 2024)
Positioning and differentiation of Serbian cuisine among other ethnic cuisines can be the means to include Serbian gastronomy in heritage and cultural tourism. This paper’s significance lies in its comparative analysis, specifically examining the impacts of taste and quality of food, food service quality, and the authenticity of national food. The goal is to identify the primary factors influencing the perceived image of Serbian national cuisine, ultimately leading to the successful development of gastronomic offerings. The research was conducted on a sample of 217 respondents. Data were collected using the survey method. Respondents expressed their level of agreement with questionnaire items on a seven-point Likert scale. Reliability, validity, and model fit were assessed in the data analysis. A structural equation modeling was used to test causal relations between the latent variables. The research results emphasize the taste and quality of food as the main driver of the perceived image of national cuisine.